Regional Dynamics on Anxiety Levels among Female Elite Soccer Players in Manipur and Tripura (American Journal of Physical Education and Health Science, 2024)
Elite athletes’ psychological well-being is said to play a significant role in their competitive nervousness, taking into account factors like performance anxiety, fear of failing, and pre-game anxiety. Even while research on anxiety in sports has advanced significantly, there hasn’t been much attention paid to female elite football players in Manipur and Tripura. The purpose of the study is to study explore the complex relationship between anxiety and football performance of elite female players of Manipur and Tripura. Forty-two female athletes, aged 18-25, representing national tournaments for their respective states (21 from Manipur and 21 from Tripura), were purposively selected for the study. The Competitive State Anxiety Inventory-2 (CSAI-2) was employed to measure three dimensions of anxiety: somatic anxiety, cognitive anxiety, and self-confidence. Descriptive statistics and the Mann-Whitney U test were utilized for data analysis. Results revealed variations in anxiety levels between the two groups. Tripura Sports School exhibited higher somatic anxiety, while YWC Manipur displayed higher cognitive anxiety and self-confidence. The study suggests that differences in training facilities, competitive exposure, and regional disparities may contribute to the observed variations in anxiety levels. The findings underscore the importance of a holistic approach to athlete development, integrating mental health support with physical training. Coaches, sports organizations, and policymakers should consider these insights when designing programs and implementing mental health initiatives for female elite soccer players in diverse regional contexts.